Geochemical Characterization of Silica Sand in the Sidenreng Rappang Area Based on X-Ray Diffraction Analysis and X-Ray Fluorescence Analysis - Suriyanto Bakri; Muhammad Anas; Muhamad Hardin Wakila; Citra Aulian Chalik (CV Insight Publisher, 2023)
Silica sand is one of the mineral materials whose presence in nature is very abundant and can be utilized in various applications, but this material is still mixed with other elements. In the chemical element on the periodic table silica is symbolized (Si). The purpose of this study was to determine the types of minerals present in silica sand and to determine the percentage of silica sand mineral content. The research location is in the area of ​​Sidenreng Rappang Regency, Sidrap is a district in South Sulawesi Province, Indonesia. This research method uses XRD and XRF analysis methods. From the results of research on minerals contained in silica sand, among others, Albite and pyroxene. With mineral content that predominates in silica sand, among others, the albite mineral from sample 1 is 23.2%, sample 2 is 32.2% and sample 3 is 13.5% while the Pyroxene mineral from sample 1 is 17.6%. , sample 2 of 13.5% and sample 3 of 17.0%.